Polynomial Least Squares Method for the Solution of Nonlinear Volterra-Fredholm Integral Equations - Bogdan Căruntu (Mathematical Problems in Engineering, 2014)
The present paper presents the application of the polynomial least squares method to nonlinear integral equations of the mixed Volterra-Fredholm type. For this type of equations, accurate approximate polynomial solutions are obtained in a straightforward manner and numerical examples are given to illustrate the validity and the applicability of the method. A comparison with previous results is also presented and it emphasizes the accuracy of the method.